Peran dalam Meningkatkan Kinerja dan Daya Saing UMKM Ekonomi Digital - Angraini Angraini; Masyuri Masyuri (Journal of Economics, Management, and Accounting, 2026)
The development of the digital economy has brought about structural changes in the management of micro, small, and medium-sized enterprises (MSMEs) through the integration of digital technology, business information systems, and digital platform-based marketing strategies. This study aims to analyze the role of the digital economy in improving the performance and competitiveness of MSMEs through a literature review using descriptive-qualitative methods and interpretive-comparative analysis. Data sources were obtained from various national and international scientific articles discussing digital transformation, digital marketing, technological innovation, digital literacy, and MSME competitiveness for the period 2021–2026. The findings indicate that digital transformation contributes to improved operational efficiency, expanded market access, strengthened consumer engagement, and increased business productivity through the utilization of social media, marketplaces, and digital payment systems. Digital marketing also strengthens SMEs’ ability to build market positioning and data-driven business strategies. Nevertheless, low digital literacy, limited technological infrastructure, and disparities in human resource competencies remain the primary obstacles in the digitalization process of SMEs in Indonesia..